ANALISIS DAMPAK LALU LINTAS DI PASAR TRADISIONAL BINTORO DEMAK DI JALAN SULTAN FATAH DEMAK - Widyiati, Khofifah Ayu Retno; Saputro, ST., MT., Yayan Adi; Hidayati, Nor; Roehman, Fatchur (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2024)
Demak City is a leading city center which is currently experiencing comprehensive development in all sectors. The increasing traffic volume on Jalan Sultan Fatah in front of Bintoro Demak Market, Demak District, Demak Regency, Central Java, is thought to be caused by busy market activity in the surrounding area. To determine the road's ability to fulfill its function, research was conducted to determine the area of side obstacles along Jl. Sultan Fatah. This research aims to assess the capacity and level of road saturation on Jl. Sultan Fatah. This research uses primary data, namely data collected directly from the field through administering questionnaires. The duration of the survey lasts for six consecutive days, namely Monday to Saturday, starting on July 24 and ending on July 29 2023. At the post-location survey and data management data collection stage, the data undergoes processing. to ascertain some road characteristics. These characteristics include traffic volume, road capacity, traffic flow speed, degree of saturation, side obstacle class, and instantaneous speed. The degree of saturation is set at 0.54 which indicates compliance with the specified threshold of 0.75. Keyword: Traffic Volume, Roads, Parking, Congestion, Markets.